Optimal monitoring to implement clean technologies when pollution is random - Inés Macho-Stadler; David Pérez-Castrillo (Center for Economic Studies and ifo Institute (CESifo), 2007)
We analyze a model where firms chose a production technology which, together with some random event, determines the final emission level. We consider the coexistence of two alternative technologies: a clean technology, and a dirty technology. The environmental regulation is based on taxes over reported emissions, and on penalties over unreported emissions. We show that the optimal inspection policy is a cut-off strategy, for several scenarios concerning the observability of the adoption of the clean technology and the cost of adopting it. We also show that the optimal inspection policy induces the firm to adopt the clean technology if the adoption cost is not too high, but the cost levels for which the firm adopts it depend on the scenario.
Keywords: K32; K42; D82; 330; Umweltpolitik; Kontrolle; Umweltbelastung; Fertigungstechnik; Technologiewahl; Umweltschutz; Ökosteuer; Theorie